Dampak Kebijakan Insentif Pajak Penghasilan Pasal 21 Di Masa Pandemi COVID-19 Terhadap Penerimaan Pajak - N Heriyah (LPPM Universitas Informatika dan Bisnis Indonesia, 2022)
Several policies issued by the government were carried out to minimize the rate of development of the Covid-19 outbreak faster. One of the policies carried out in terms of restrictions on public space for movement by governments around the world is aimed at inhibiting the spread of the Covid-19 virus, including Indonesia. The policies carried out by the government, especially in fiscal policy, have been given to respond in response to the low purchasing power of the people as a result of the impact of the Covid-19 pandemic, one of which is by providing tax incentives in terms of reducing tax rates. This research is an associative research that serves to explain or predict between tax incentives as an independent variable to the dependent variable, namely tax revenue. The object of this research is Income Tax Article 21 on the dependent variable, namely tax revenue. The technique used is statistical technique or quantitative technique. This study uses secondary data in the form of individual taxpayer data. The results showed that the PPh 21 incentive (Income Tax Ps 21) had no significant effect on tax revenue.